ASPEK LEGALITAS KESELAMATAN KAPAL DI DANAU TOBA - Richard Christian (Fakultas Hukum Universitas Kristen Indonesia, 2020)
Lake Toba's readiness as an international standard tourist destination must be supported by the safety aspects of shipping and tourism.The characteristics of Lake Toba's aquatic environment are still a mystery, the availability of data, documentation of the waters, publication, maps issued from relevant agencies in Indonesia is not available completely. If the ship’s master as the highest leader on board sails the ship with minimal information taken from local information or even hereditary from the community around the voyage that is carried out it will be very risky. The accident of ship Sinar Bangun has become a benchmark for shipping safety in Indonesia, especially for ships that sail in the mainland shipping area. The Indonesian National Shipping Act provides rules related to river and lake transportation. “Pas Sungai Danau” is a certificate given to ships that sail specifically in the river and lake navigation areas. Keyword: tourist destination, aquatic environment, lake transportation